Transposable element dynamics in Xenopus laevis embryogenesis: a tale of two coexisting subgenomes - Edith Tittarelli; Elisa Carotti; Federica Carducci; Marco Barucca; Adriana Canapa; Maria Assunta Biscotti (Mobile DNA)
Abstract The African clawed frog Xenopus laevis has an allotetraploid genome consisting of two subgenomes referred as L relating to the Long chromosomes and S relating to the Short chromosomes. While the L subgenome presents conserved synteny with X. tropicalis chromosomes, the S subgenome has undergone rearrangements and deletions leading to differences in gene and transposable element (TE) content between the two subgenomes. The asymmetry in the evolution of the two subgenomes is also detectable in gene expression levels and TE mobility. TEs, also known as “jumping genes”, are mobile genetic elements having a key role in genome evolution and gene regulation. However, due to their potential deleterious effects, TEs are controlled by host defense mechanisms such as the nucleosome remodeling and deacetylase (NuRD) complex and the Argonaute proteins that mainly modify the heterochromatin environment. In embryogenesis, TEs can escape the silencing mechanisms during the maternal-to-zygotic transition when a transcriptionally permissive environment is created. Moreover, further evidence highlighted that the reactivation of TEs during early developmental stages is not the result of this genome-wide reorganization of chromatin but it is class and stage-specific, suggesting a precise regulation. In line with these premises, we explored the impact of TE transcriptional contribution in six developmental stages of X. laevis. Overall, the expression pattern referred to the entire set of transcribed TEs was constant across the six developmental stages and in line with their abundance in the genome. However, focusing on subgenome-specific TEs, our analyses revealed a distinctive transcriptional pattern dominated by LTR retroelements in the L subgenome and LINE retroelements in the S subgenome attributable to young copies. Interestingly, genes encoding proteins involved in maintaining the repressive chromatin environment were active in both subgenomes highlighting that TE controlling systems were active in X. laevis embryogenesis and evolved symmetrically.